2016
DOI: 10.1007/s11999-016-4955-4
|View full text |Cite
|
Sign up to set email alerts
|

Hindfoot Arthrodesis with the Blade Plate: Increased Risk of Complications and Nonunion in a Complex Patient Population

Abstract: Background Previous hindfoot surgeries present a unique challenge to hindfoot arthrodesis, as the patients may have multiple incisions around the hindfoot. In high-risk patients with compromised soft tissues, a posterior approach can provide an alternative for a fresh soft tissue plane for the surgery. The use of a blade plate construct is widely accepted; however, there are limited data supporting the use of a posterior approach. Questions/purposes We asked (1) what proportion of patients treated with this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Osteotomy fusion was defined as satisfying clinical criteria (no pain, no warmth, improvement in swelling, and stability to stress) and radiographic criteria (visible trabecular bridging across the osteotomy site and no lucency around the hardware). 13 Hindfoot alignment was assessed by measurement of the tibial ankle surface (TAS) angle, the tibiotalar (TT) angle, and TLS angle (Figure 4). 4,36 The talar position within the ankle mortise was calculated as the difference between the TAS and TT angles on AP weightbearing ankle radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…Osteotomy fusion was defined as satisfying clinical criteria (no pain, no warmth, improvement in swelling, and stability to stress) and radiographic criteria (visible trabecular bridging across the osteotomy site and no lucency around the hardware). 13 Hindfoot alignment was assessed by measurement of the tibial ankle surface (TAS) angle, the tibiotalar (TT) angle, and TLS angle (Figure 4). 4,36 The talar position within the ankle mortise was calculated as the difference between the TAS and TT angles on AP weightbearing ankle radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies by Gorman and colleagues showed fusion in 73% of patients operated on with a posterior plate within 6 months following surgery, although 10% had delayed union after 6 months and 18% had nonunion. 8 Another retrospective study showed 78% fusion and 22% non-union in 9 patients who underwent tibiotalocalcaneal fusion with a posterior anatomic plate. 15 In our study, the fusion rate was 95% at a mean follow-up of 38 months (range, 3-87 months).…”
Section: Discussionmentioning
confidence: 97%
“…17,[44][45][46][47][48] Studies looking at prognostic factors of outcomes of TTC fusions specifically with femoral head allografts have generally not identified factors that correlated with outcomes. 3,14,49,50 No previous studies were found that identified being male or a lateral operative approach as negative influencers of TTC fusion outcomes. Operative approach was addressed by Berkowitz et al, 16 who noted that the anterior approach had the advantages of allowing for substantial correction of malalignment and sparing of the lateral malleolus, which may improve rotational alignment, increase overall stability of the construct, and avoid future valgus malalignment.…”
Section: Discussionmentioning
confidence: 99%